PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN PROVINSI RIAU - Lovina Lovina; Susi Hendriani; Marnis Marnis (Institut Bisnis dan Teknologi Pelita Indonesia, 2017)
The purpose of this research were 1) To know and analyze the effect on the performance leadership through employee organizational commitment at Dinas Pendapatan Provinsi Riau. 2) Was there a leadership influence on performance through employee organizational culture at Dinas Pendapatan Provinsi Riau. 3) Was there any influence of leadership on organizational commitment through organizational culture at Dinas Pendapatan Provinsi Riau. 4) Was there any influence of leadership, organizational culture, and organizational commitment partially to employee performance at Dinas Pendapatan Provinsi Riau.The use of quantitative approaches in research in a way to build / acquire knowledge that is based on objectivity and controls that operate with strict rules. The method used in this research is survey method with path analysis techniques. The population in this study were all employees of the Dinas Pendapatan Provinsi Riau totaling 440 people. The sampling technique in this research is to use a proportional stratified sampling. Determination of the number of samples is done by using the formula specified slovin with a precision of 5%. Thus the sample in this study amounted to 210 employees Dinas Pendapatan Provinsi Riauwere drawn at random, the data collection techniques used in this study is based on variables studied were the questioner. The purpose of this research were 1) To know and analyze the effect on the performance leadership through employee organizational commitment at Dinas Pendapatan Provinsi Riau. 2) Was there a leadership influence on performance through employee organizational culture at Dinas Pendapatan Provinsi Riau. 3) Was there any influence of leadership on organizational commitment through organizational culture at Dinas Pendapatan Provinsi Riau. 4) Was there any influence of leadership, organizational culture, and organizational commitment partially to employee performance at Dinas Pendapatan Provinsi Riau.The use of quantitative approaches in research in a way to build / acquire knowledge that is based on objectivity and controls that operate with strict rules. The method used in this research is survey method with path analysis techniques. The population in this study were all employees of the Dinas Pendapatan Provinsi Riau totaling 440 people. The sampling technique in this research is to use a proportional stratified sampling. Determination of the number of samples is done by using the formula specified slovin with a precision of 5%. Thus the sample in this study amounted to 210 employees Dinas Pendapatan Provinsi Riauwere drawn at random, the data collection techniques used in this study is based on variables studied were the questioner.